Dunaliella salina fuel blends as the secondary fuel for the microgas turbine engines: A combustion and emission study. (15th July 2023) - Gokulnath, R.; Booma Devi, P.; Gavurova, Beata; Ali Alharbi, Sulaiman; Alfarraj, Saleh; Jhanani, G.K.; Brindhadevi, Kathirvel
Highlights: Dunaliella salina blends tested in the micro gas turbine engine. Thermal efficiency of the engine has been effectively increased. Highest thermal efficiency was noticed in DSJB50% while the lowest was seen in the fuel of DSJB0%. Significant decrease in the emissions of NO and CO were noted at equivalence ratio. Abstract: With the increasing demand for fossil fuels causing a decline in oil resources, the development of bio-gasoline has the potential to reduce the dependence of the fuel market on fossil fuels. This paper presents the experimental results of performance and emission characteristics of biofuel in a micro gas turbine engine. The microalgae chosen for this study is Dunaliella salina and different blends includes DB0 (Jet A fuel 100% + Dunaliella salina 0%), DB25 (Jet A fuel 75% + Dunaliella salina 25%) and DB50 (Jet A fuel 50% +  Dunaliella salina 50%). All experimental tests were conducted in a small test rig and at different engine speeds as 40000 rpm, 50000 rpm and 60000 rpm. The study analysed the performance metrics including thrust, thrust-specific fuel consumption, thermal efficiency, and emissions. Results showed that blends reduced static thrust and thrust-specific fuel consumption and enhanced thermal efficiency. At 55000 rpm, the DB25 and DB50 reported 3% and 15% reduction in the static thrust. However, 11% and 15% reduction in the TSFC has been noted respectively. The CO and NOx emissions were also reduced with the use of biofuels. There was no observed decrease in NOx production. As the concentration of the microalgae blends increases, the temperature in the combustion chamber also increased, leading to an increase in NOx production. The findings indicate that blending microalgae blends with Jet-A fuel can lower pollutant emissions while retaining the desired thrust level. This research suggests that an optimal blend of the two fuels can be found and that biofuels can be a viable alternative to petroleum-based energy.